Ni(Co)@NC magnetic nanocomposite, preparation method and application thereof
Patent Information
- Application Number
- CN202410486644.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-23
AI Technical Summary
近年来,其安全性有所改善,但成本高,使用年限约为5~10年,每年都会淘汰大量的钴酸锂电池
[0020](1)本发明采用两步溶剂热+氮气氛围保护下高温热解的方法制备得到Ni(Co)@NC磁性纳米复合材料,相对简易的一锅溶剂热法制备的复合材料,具有显著的抗生素活化降解效果,且制备方法简单、操作方便,所制备的复合材料具有回收性能好、催化效率高的优点,能够高效活化过硫酸盐降解废水中的抗生素,pH影响较小,金属离子溶出量少,污染小,稳定性和重复性好,成本低,是一种具有很高潜在应用价值和商业价值的催化材料。
Smart Images

Figure CN118527166B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wastewater treatment technology, and particularly relates to a Ni(Co)@NC magnetic nanocomposite material, its preparation method and application. Background Technology
[0002] With the rapid development of industrial technology, water pollution has become increasingly serious, with antibiotic-related water pollution accounting for half of the problem. Residual antibiotics in water cause severe environmental pollution and damage to human health. Long-term presence in the environment may lead to antibiotic resistance in bacteria and viruses, potentially resulting in superbugs that pose a deadly threat to human health.
[0003] Traditional treatment processes for antibiotics in water generally suffer from drawbacks such as high cost, slow reaction time, potential for secondary pollution, and difficulty in treating low-concentration wastewater. In contrast, advanced oxidation technologies (AOs) can degrade antibiotics into smaller molecules, thereby mitigating their harm to ecosystems. Among these, sulfate-based AOs generate sulfate radicals with strong oxidizing power and long lifespan. However, most materials used to activate permonosulfate (PMS) are centrifuged using traditional methods, which are cumbersome and prone to mass loss during material recovery. Therefore, the widespread application of magnetic materials in pollutant degradation is of practical significance.
[0004] Magnetic materials have long been used to degrade pollutants through advanced oxidation. Transition metal oxides, spinel ferrite, and transition metal-doped carbon-based materials can effectively activate PMS. Transition metal-doped carbon-based materials possess stable framework structures, good environmental friendliness, and excellent magnetic properties. Compared to transition metal oxides and spinel ferrite, they can reduce the leaching of heavy metal ions during catalytic degradation. Based on experimental findings, M@NC (M = Fe, Co, Ni, etc.) derived from metal-organic frameworks (MOFs) are nitrogen-doped carbon-based materials with multiple valence states of transition metal inlay, showing great potential in activating PMS to degrade pollutants. These materials are also magnetic and exhibit excellent performance in terms of easy recycling and reuse after use. Ni@NC derived from Ni-2-AA is a Ni (Ni-2-AA) material with three valence states. 0 Ni 2+ Ni 3+ Nitrogen-doped carbon-based materials have been shown to promote electron transfer efficiency and the generation of strong oxidative radicals during the activation of PMS for the advanced oxidation treatment of emerging pollutants. However, the electron transfer rate of a single element is limited, which is detrimental to the generation of high-energy radicals during PMS activation. Therefore, it is imperative to seek bimetallic-attached nitrogen-doped carbon-based composite materials.
[0005] As is well known, lithium cobalt oxide batteries are structurally stable, have high specific capacity, and outstanding overall performance, making them widely used in small electronic devices such as laptops, mobile phones, and MP3 / 4 players. In recent years, their safety has improved, but their high cost and limited lifespan of approximately 5-10 years mean that a large number of lithium cobalt oxide batteries are phased out every year. Cobalt is a relatively scarce strategic metal, making its recycling and application imperative.
[0006] Therefore, utilizing waste lithium cobalt oxide batteries to prepare a magnetic nanocomposite material that can efficiently treat antibiotics in the aquatic environment has high application and commercial value. Summary of the Invention
[0007] To address the shortcomings mentioned in the background art, this invention provides a Ni(Co)@NC magnetic nanocomposite material, its preparation method, and its application. A highly efficient Ni(Co)@NC magnetic composite catalyst for catalyzing persulfate is prepared by utilizing a recycled cobalt source combined with a two-step solvothermal process and high-temperature pyrolysis. This solves the current application bottlenecks such as the difficulty in recycling and reusing catalysts, narrow pH application range, and low oxidant utilization rate.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing Ni(Co)@NC magnetic nanocomposite material, the method comprising the following steps:
[0010] (1) After fully dissolving 2-aminoterephthalic acid, nickel nitrate and N,N-dimethylformamide, a solvothermal reaction was carried out. After the reaction was completed, the temperature was automatically lowered and cooled. Then, Ni-MOF was obtained by centrifugation, washing and drying.
[0011] (2) Discharge the waste lithium cobalt oxide battery, dry it and disassemble it. Remove the electrodes and shell and then dissolve the aluminum film. Then wash, dry and calcine at high temperature to obtain black active material. Add the black active material to citric acid solution and slowly leach it. At the same time, slowly add a small amount of hydrogen peroxide to promote leaching to obtain cobalt citrate.
[0012] (3) The Ni-MOF, cobalt citrate and N,N-dimethylformamide were mixed and dispersed and then subjected to a solvothermal reaction. After the reaction was completed and the mixture was allowed to cool naturally, it was centrifuged, washed and dried to obtain Ni(Co)-MOF.
[0013] (4) The Ni(Co)-MOF was pyrolyzed at high temperature in a nitrogen atmosphere to obtain Ni(Co)@NC magnetic nanocomposite material.
[0014] Preferably, the solvothermal reaction conditions for preparing the Ni-MOF and Ni(Co)-MOF are: 160-180℃, held for 12-24h.
[0015] Preferably, in step (4), the conditions for high-temperature pyrolysis are: 400-800℃, pyrolysis for 4 hours.
[0016] The Ni(Co)@NC magnetic nanocomposite material prepared by this invention is in the form of nanoparticle powder. In this powder, multivalent Ni and Co are embedded in nitrogen-doped carbon layer material to form a diatomic metal catalyst. While activating PMS to generate high-energy free radicals, it also undergoes valence state cycling, increasing the redox active sites of Ni(Co)@NC magnetic nanocomposite material and accelerating redox. In the redox valence state cycling, PMS is further activated to continuously generate more high-energy free radicals, accelerating the decomposition of PMS and the generation of active free radicals, thereby accelerating and efficiently mineralizing emerging pollutants.
[0017] Preferably, in the Ni(Co)@NC magnetic nanocomposite material, the molar ratio of Co to Ni is 0.1:1 to 5:1.
[0018] This invention further provides the Ni(Co)@NC magnetic nanocomposite material for activating persulfate degradation of antibiotics in wastewater. It has high catalytic degradation efficiency, easy recovery, high reusability, minimal pH impact, low metal ion dissolution, low pollution, good stability and repeatability, and low cost. It is a catalyst that can be widely used and can efficiently remove antibiotics from water.
[0019] Compared with the shortcomings and deficiencies of existing technologies, the present invention has the following beneficial effects:
[0020] (1) The present invention uses a two-step solvothermal + high-temperature pyrolysis method under nitrogen atmosphere protection to prepare Ni(Co)@NC magnetic nanocomposite material. The composite material prepared by the relatively simple one-pot solvothermal method has a significant effect on antibiotic activation and degradation. The preparation method is simple and easy to operate. The prepared composite material has the advantages of good recovery performance and high catalytic efficiency. It can efficiently activate persulfate to degrade antibiotics in wastewater with little pH influence, low metal ion dissolution, low pollution, good stability and repeatability, and low cost. It is a catalytic material with high potential application value and commercial value.
[0021] (2) In the Ni(Co)@NC magnetic nanocomposite material prepared by the present invention, Ni and Co nanoparticles are embedded on nitrogen-doped carbon layer material, so that Ni(Co)@NC magnetic nanocomposite material has good magnetic properties, thereby enhancing the repeatability of composite material.
[0022] (3) In the Ni(Co)@NC magnetic nanocomposite material prepared by the present invention, Ni and Co nanoparticles are embedded on the nitrogen-doped carbon layer material, so that it can carry out redox cycle while activating PMS to generate high-energy free radicals. This process continuously generates electrons and provides abundant active sites for activating PMS through carbon-based materials, thereby promoting charge transfer and enhancing the ability to degrade antibiotics. Attached Figure Description
[0023] Figure 1 (a) shows the XRD patterns of Ni-2-AA, Ni@NC-400, Ni@NC-500, Ni@NC-600, Ni@NC-700 and Ni@NC-800; Figure 1 (b) shows the effect of Ni@NC-400, Ni@NC-500, Ni@NC-600, Ni@NC-700 and Ni@NC-800 activating PMS to degrade ENR.
[0024] Figure 2 (a) is the XRD pattern of Co-2-AA, Ni(Co)-2-AA-1, Ni(Co)-2-AA-2, Ni(Co)-2-AA-3, and Ni(Co)-2-AA-4; Figure 2 (b) shows the XRD patterns of Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4; Figure 2 (c) is a graph showing the effect of Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4 activating PMS to degrade ENR.
[0025] Figure 3 (a) shows the XRD patterns of Ni(Co)-2-AA-3-one-pot and Ni(Co)@NC-3-one-pot; Figure 3 (b) is a graph showing the effect of Ni(Co)-2-AA-3-one-pot and Ni(Co)@NC-3-one-pot activating PMS to degrade ENR.
[0026] Figure 4 This is the VSM diagram for Ni@NC and Ni(Co)@NC.
[0027] Figure 5 (a) is the SEM image of Ni(Co)@NC; Figure 5 (b) is the TEM image of Ni(Co)@NC. Figure 5 (c) is the HRTEM plot of Ni(Co)@NC.
[0028] Figure 6This is a comparison chart of the activation and degradation of ENR by Ni@NC, Ni(Co)@NC, and PMS under different conditions.
[0029] Figure 7 (a) is a cyclic degradation diagram of the Ni(Co)@NC / PMS / ENR system; Figure 7 (b) shows the XRD patterns of the catalyst Ni(Co)@NC in the Ni(Co)@NC / PMS / ENR system before and after cycling.
[0030] Figure 8 (a) is a catalytic degradation diagram of enrofloxacin in different water qualities by the Ni(Co)@NC / PMS / ENR system; Figure 8 (b) is a diagram showing the activation and degradation of different organic pollutants by the Ni(Co)@NC / PMS / POL system. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0032] 1. Preparation of Ni(Co)@NC magnetic nanocomposites:
[0033] 1.1 Preparation of Ni-MOF by solvothermal method:
[0034] 5 mmol of 2-aminoterephthalic acid (2-AA) and 5 mmol of Ni(NO3)2·6H2O were added to 65 mL of N,N-dimethylformamide (DMF) solvent and dissolved completely. The mixture was kept at 160 °C for 24 h. After the solvothermal reaction was completed, the mixture was naturally cooled, centrifuged, washed, dried, and then milled to obtain Ni-MOF (also known as Ni-2-AA).
[0035] 1.2 Discussion on the optimal temperature for Ni@NC preparation by pyrolysis under nitrogen atmosphere:
[0036] The prepared Ni-MOF was placed in a programmed tube furnace under nitrogen atmosphere protection, with a programmed heating rate of 5℃ / min. The furnace was held at 400℃, 500℃, 600℃, 700℃, and 800℃ for 4 hours, respectively. After natural cooling and milling, Ni@NC-400, Ni@NC-500, Ni@NC-600, Ni@NC-700, and Ni@NC-800 were obtained. By setting the above pyrolysis temperatures, Ni@NC prepared at different pyrolysis temperatures was obtained, and the effect of carbonization temperature on catalytic performance was explored. It is well known that nickel has three oxides. Ni2O3 is stable only at low temperatures, dissociating into Ni3O4 when heated to 400–500℃, and ultimately converting to NiO when the temperature is further increased. Combined with the activation and degradation experiments of the Cat / PMS / POL system, Ni@NC-500 showed the best activation effect on PMS. Therefore, 500℃ was used as the pyrolysis temperature under nitrogen atmosphere protection in subsequent experiments.
[0037] 1.3 Extraction of cobalt citrate from spent lithium cobalt oxide batteries:
[0038] After being discharged, disassembled, and dried, discarded lithium cobalt oxide batteries from mobile phones were slowly added to a sodium hydroxide solution for pyrolysis of the aluminum film. After complete reaction, the mixture was filtered, washed, dried, calcined at 550°C, and ground to obtain a black active material. The black active material was then added to a citric acid solution at 90°C for leaching, with a small amount of hydrogen peroxide injected to promote leaching. After thorough leaching, the cobalt-containing cobalt citrate leachate was filtered and reserved for use. Experimental data showed that the cobalt citrate concentration in the citric acid leachate was 0.169 mol / L.
[0039] 1.4 Discussion on the optimal ratio of Ni(Co)@NC magnetic nanocomposites:
[0040] After thorough shaking, 5 mmol of Ni-MOF, four gradient amounts of cobalt citrate leaching solution (0.12 mmol, 0.24 mmol, 0.36 mmol, and 0.48 mmol), and 55 mL of DMF were subjected to a second solvothermal reaction at 160 °C for 24 h. Following the solvothermal reaction, the mixture was naturally cooled, centrifuged, washed, dried, and milled to obtain four Ni(Co)-MOFs (also denoted as Ni(Co)-2-AA), named Ni(Co)-2-AA-1, Ni(Co)-2-AA-2, Ni(Co)-2-AA-3h, and Ni(Co)-2-AA-4, respectively. Simultaneously, Co-2-AA was prepared using the same method, but without the addition of Ni-2-AA. However, due to the extremely low yield and poor crystallinity of Co-2-AA, it was not subsequently prepared and used in Co@NC.
[0041] Ni(Co)-2-AA-1, Ni(Co)-2-AA-2, Ni(Co)-2-AA-3, and Ni(Co)-2-AA-4 were placed in a programmed tube furnace under nitrogen atmosphere protection. The programmed heating rate was set to 5℃ / min, and the furnace was held at 500℃ under nitrogen atmosphere protection for 4 hours. After natural cooling and milling, Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4 were obtained.
[0042] 2. Advantages of the preparation method of this invention based on the degradation rate of pollutants.
[0043] Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4 were used to activate PMS to degrade ENR, respectively. Degradation experiments showed that Ni(Co)@NC-3 activated PMS had the best effect on ENR degradation, with a degradation rate as high as 98.36%. Based on this, a one-pot solvothermal method was used to prepare Ni(Co)-2-AA-3-one-pot, and then Ni(Co)@NC-3-one-pot was prepared for comparison. The specific method is as follows: 5 mmol Ni(NO3)2·6H2O, 5 mmol 2-aminoterephthalic acid (2-AA), 0.36 mmol cobalt citrate immersion solution, and 55 mL DMF were thoroughly mixed and kept at 160℃ for 24 h. After solvothermal treatment, the mixture was naturally cooled, centrifuged, washed, dried, and milled to obtain Ni(Co)-2-AA-3-one-pot. Ni(Co)-2-AA-3-one-pot was placed in a nitrogen-protected programmed tube furnace with a programmed heating rate of 5℃ / min and kept at 500℃ for 4 h. After natural cooling and milling, Ni(Co)@NC-3-one-pot was obtained. The degradation rate was confirmed to be only 35.19% by the activated PMS degradation ENR experiment. This shows that the activation effect of Ni(Co)@NC-3-one-pot prepared by the relatively simple one-pot solvothermal method is far inferior to that of Ni(Co)@NC-3.
[0044] 3. Sample testing and characterization
[0045] (1) The XRD diffraction patterns of the prepared Ni@NC and Ni(Co)@NC are as follows: Figure 1 (a) and Figure 2 As shown in (b), the prepared products all exhibit good crystallinity, indicating successful material preparation. The XRD patterns and activation degradation ENR diagrams of the prepared Ni(Co)-2-AA-3-one-pot and Ni(Co)@NC-3-one-pot are shown in Figures (b). Figure 3 (a) and Figure 3As shown in (b), the results showed that Ni(Co)-2-AA-3-one-pot had poor crystallinity, similar to that of Ni-2-AA. This indicates that the one-pot solvothermal method could not successfully prepare Ni(Co)-2-AA-3. Although Ni(Co)@NC-3-one-pot had better crystallinity, a comparison of the XRD patterns of Ni@NC and Ni(Co)@NC revealed that the Co content was extremely low, which further confirms that the one-pot solvothermal method is not feasible.
[0046] (2) The VSM spectra of the prepared Ni@NC and Ni(Co)@NC are as follows: Figure 4 As shown, the introduction of Co increases the magnetism of Ni(Co)@NC compared to Ni@NC. This is attributed to the fact that the multivalent Co can provide enough electrons to promote the conversion of PMS into high-energy free radicals, thereby efficiently degrading ENR.
[0047] (3) The SEM, TEM, and HRTEM test results of the prepared Ni(Co)@NC are as follows: Figure 5 (a) Figure 5 (b) and Figure 5 As shown in (c), the prepared Ni(Co)@NC magnetic nanocomposite material is in the form of sheet-like blocks, with a rough surface structure composed of irregularly aggregated nanoparticles. Ni and Co nanoparticles are embedded in the nitrogen-doped carbon layer material.
[0048] 4. Degradation experiment
[0049] Enrofloxacin (ENR) was used as an antibiotic in water. 0.010 g of ENR was dissolved in 1000 mL of water to prepare water to be treated. The concentration of the antibiotic solution to be treated was 0.010 g / L.
[0050] (1) Five activation degradation experiments were conducted using Ni@NC-400, Ni@NC-500, Ni@NC-600, Ni@NC-700, and Ni@NC-800 as catalysts. First, the five groups of water to be treated were placed in transparent reaction vessels. The corresponding degradation material was added to each group of water, along with persulfate (PMS). The water was then magnetically stirred. After a certain reaction time, the water was filtered. The degradation results are shown below. Figure 1 As shown in (b), the degradation rates of ENR by Ni@NC-400, Ni@NC-500, Ni@NC-600, Ni@NC-700, and Ni@NC-800 within 60 minutes were 51.70%, 62.27%, 55.51%, 54.69%, and 47.85%, respectively. The results indicate that a higher nitrogen atmosphere pyrolysis temperature is not necessarily better for Ni-2-AA. Furthermore, in the activated degradation system, the presence of multiple valence states of Ni can form Ni... 0←→Ni 2+ ←→Ni 3+ Cycling promotes the generation and consumption of electrons in the Cat / PMS / POL system. As the degradation data shows, Ni@NC prepared at 500℃ exhibits the best performance. Therefore, the subsequent nitrogen atmosphere pyrolysis temperature was selected as 500℃.
[0051] (2) Ni@NC-500 prepared without cobalt citrate leaching solution was designated as Ni(Co)@NC-0. Five activation degradation experiments were conducted using Ni(Co)@NC-0, Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4 as catalysts. The five groups of water to be treated were placed in transparent reaction vessels. The corresponding degradation material was added to each group of water, along with persulfate (PMS). The water was then magnetically stirred. After a certain reaction time, the water was filtered. The degradation results are as follows: Figure 2 As shown in (c), the degradation rates of ENR by Ni(Co)@NC-0, Ni(Co)@NC-1, Ni(Co)@NC-2, Ni(Co)@NC-3, and Ni(Co)@NC-4 within 30 minutes were 59.81%, 88.87%, 91.34%, 98.36%, and 97.62%, respectively. The results indicate that partial substitution of Ni in Ni-2-AA is not necessarily better the higher the substitution ratio. The catalyst performance improved as the Co addition increased from 0 to 0.36 mmol. However, when the Co addition was 0.48 mmol, the effect decreased slightly compared to 0.36 mmol. This may be because with the increase in Co addition, some Co aggregated, leading to a decrease in activation efficiency.
[0052] (3) The activation degradation ENR experiment was performed using Ni(Co)@NC-3-one-pot, and the degradation results are as follows: Figure 3 As shown in (b), although its preparation is slightly simpler than that of Ni(Co)@NC-3, its activation and degradation effect on PMS is significantly worse than that of Ni(Co)@NC-3. This may be because the unique framework structure of Ni-MOF (Ni-2-AA) was not formed during the one-pot solvothermal preparation process, and no specific structure similar to Ni(Co)@NC-3 was formed after nitrogen atmosphere pyrolysis. Therefore, it cannot achieve the high-efficiency activation performance of Ni(Co)@NC-3. Thus, Ni(Co)-2-AA-3 cannot be synthesized by the relatively simple one-pot solvothermal method.
[0053] (4) Using Ni(Co)@NC (Ni(Co)@NC-3) as a catalyst, PMS as an advanced oxidant, and ENR as a representative of emerging pollutants, four sets of degradation comparison experiments were conducted. The degradation results at 30 min are as follows: Figure 6As shown, the self-degradation rate of ENR is only 1.87%, the degradation rate of PMS / ENR system is only 14.11%, and the degradation rate of Ni(Co)@NC / ENR system is only 2.70%, while the degradation rate of Ni(Co)@NC / PMS / ENR system is as high as 98.36%, which fully demonstrates the high activation efficiency of Ni(Co)@NC.
[0054] 5. Practical applications of Ni(Co)@NC magnetic nanocomposites
[0055] The cyclic degradation diagram of the Ni(Co)@NC / PMS / ENR system is shown below. Figure 7 As shown in (a), the Ni(Co)@NC magnetic nanocomposite material still achieves an activation degradation rate of 86.60% after the 5th cycle of the "activation degradation-magnetic recovery-washing and drying-activation degradation" cycle, indicating its excellent stability and good reusability. Meanwhile... Figure 7 (b) shows the XRD patterns of Ni(Co)@NC magnetic nanocomposite before and after use. The comparison did not reveal any significant changes in the XRD of the material, indicating that Ni(Co)@NC is structurally stable, which is the intrinsic reason for its good cyclic activation effect.
[0056] To further investigate the general applicability of Ni(Co)@NC magnetic nanocomposites, ENR degradation experiments were conducted in different water bodies. The results are as follows: Figure 8 As shown in (a), the degradation rate of the Ni(Co)@NC / PMS / ENR system was over 70% in all three actual water bodies, indicating that it still plays an important role in real-world environments. The value of Ni(Co)@NC is further demonstrated in degradation experiments of different emerging pollutants. The activation degradation diagrams of the Ni(Co)@NC / PMS / POL system for different organic pollutants are shown in Figure [Figure number missing]. Figure 8 As shown in (b), the degradation effect of the Ni(Co)@NC / PMS / POL system in the degradation experiments of seven common emerging pollutants, including carbamazepine (CBZ), ciprofloxacin (CIP), chloramphenicol (GM), tetracycline (TC), levofloxacin (LVF), sulfacetamide (SA) and bisphenol A (BPA), is commendable.
[0057] In summary, this invention first uses a solvothermal method to obtain Ni-MOF (Ni-2-AA), and determines the optimal nitrogen atmosphere pyrolysis temperature for Ni@NC to be 500℃ by controlling the nitrogen atmosphere pyrolysis temperature. Secondly, cobalt citrate leachate is extracted from waste lithium cobalt oxide batteries inside mobile phones and used for solvothermal synthesis of Ni(Co)-2-AA, which is then subjected to nitrogen atmosphere pyrolysis to obtain Ni(Co)@NC. The introduction of Co increases the Co content. 0 ←→Co 2+ ←→Co 3+Cycle, while in Ni 0 ←→Ni 2+ ←→Ni 3+ In the presence of the cycle, electrons are continuously generated and consumed in the valence state cycle of Ni and Co. Nitrogen-doped carbon-based materials provide a large number of active sites as substrate materials, which accelerates the decomposition of PMS to generate high-energy free radicals, thereby accelerating the mineralization and degradation of emerging pollutants.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing Ni(Co)@NC magnetic nanocomposite material, characterized in that, The method includes the following steps: (1) After fully dissolving 2-aminoterephthalic acid, nickel nitrate and N,N-dimethylformamide, a solvothermal reaction was carried out. After the reaction was completed, the temperature was automatically lowered and cooled. Then, Ni-MOF was obtained by centrifugation, washing and drying. (2) Discharge the waste lithium cobalt oxide battery, dry it and disassemble it. Remove the electrodes and shell and then dissolve the aluminum film. Then wash, dry and calcine at high temperature to obtain black active material. Add the black active material to citric acid solution and slowly leach it. At the same time, slowly add a small amount of hydrogen peroxide to promote leaching to obtain cobalt citrate. (3) The Ni-MOF, cobalt citrate and N,N-dimethylformamide are mixed and dispersed and then subjected to a solvothermal reaction. After the reaction is completed and the mixture is allowed to cool naturally, it is centrifuged, washed and dried to obtain Ni(Co)-MOF. (4) The Ni(Co)-MOF is pyrolyzed at high temperature in a nitrogen atmosphere to obtain Ni(Co)@NC magnetic nanocomposite material; the prepared Ni(Co)@NC magnetic nanocomposite material is in the form of sheet block, which has a rough surface structure composed of irregularly aggregated nanoparticles, and Ni and Co nanoparticles are embedded on nitrogen-doped carbon layer material.
2. The method for preparing Ni(Co)@NC magnetic nanocomposite material as described in claim 1, characterized in that, The solvothermal reaction conditions for preparing the Ni-MOF and Ni(Co)-MOF are: 160-180℃, held for 12-24 h.
3. The method for preparing Ni(Co)@NC magnetic nanocomposite material as described in claim 1, characterized in that, In step (5), the conditions for high-temperature pyrolysis are: 400-800℃, pyrolysis for 4 h.
4. A Ni(Co)@NC magnetic nanocomposite material prepared by the preparation method according to any one of claims 1-3, characterized in that, In the Ni(Co)@NC magnetic nanocomposite material, multivalent Ni and Co are embedded in nitrogen-doped carbon layer material.
5. The Ni(Co)@NC magnetic nanocomposite material as described in claim 4, characterized in that, In the Ni(Co)@NC magnetic nanocomposite material, the molar ratio of Co to Ni is 0.1:1 to 5:
1.
6. The application of the Ni(Co)@NC magnetic nanocomposite material as described in claim 4 or 5 in the activation of persulfate degradation of antibiotics in wastewater.
Citation Information
Patent Citations
Metal catalyst as well as preparation method and application thereof
CN116899570A